Academic incivility on job satisfaction and depressivity: can supervisory support be the antidote?. (3rd November 2020) - Abas, Nurul Ain Hidayah; Lin, Mei-Hua; Otto, Kathleen; Idris, Izazol; Ramayah, T.
Abstract : Purpose: Academia is known for its high competitiveness, with prestige and diverse responsibilities and achievements being decisive determinants of success resulting in academic incivility. This paper extends Lazarus and Folkman's theory of stress by examining the moderating role of interpersonal justice (IJ), as supervisory support, on academics' job satisfaction and depressivity. Design/methodology/approach: The study recruited 185 academics from a public university in Malaysia to participate in a survey. Using the partial least squares- structural equation modeling (PLS-SEM) analysis, academic incivility was negatively related to job satisfaction, whilst positively related to depressivity. Findings: As hypothesized, it was found that the predicted detrimental effect of academic incivility on job satisfaction was buffered by perceiving high IJ from their immediate supervisors, i.e. deans or heads of department. An unanticipated finding was that there was a stronger relationship between academic incivility and depressivity for those academics who perceived high supervisory IJ. Practical implications: Further, academic management can formulate and revise zero-incivility policies and promote awareness explaining the detrimental impacts of incivility, despite support systems in academia. Originality/value: This study provides the first empirical evidence showing the differential impact of supervisory IJ on two conditions of incivility–well-being relationships. Work culture and various sources of incivility should be considered for future research.